The Effectiveness of FAST Method Education in Early Stroke Detection Efforts for Hypertensive Patients at Pa’betengang Community Health Center, Bantaeng - Arafah, Salmah; Dewiyanti, Dewiyanti; Ernawati, Ernawati; Kamriana, Kamriana; Oktaviana, Dina; Alwi, Alwi (Fakultas Kedokteran Universitas Jenderal Soedirman, 2025)
Stroke is a major complication of hypertension that leads to disability and death; however, knowledge among hypertensive patients regarding the early signs of stroke remains low. This study aimed to evaluate theeffectiveness of the FAST (Face, Arm, Speech, Time) educational method in improving early stroke detection skills among hypertensive patients. A one-group pre-experimental pre-post design was used involving 60 hypertensive patients at the Pa’betengang Community Health Center, Bantaeng Regency. The education was delivered in two sessions using visual media and interactive simulations. Knowledge was measured using a questionnaire administered before and after the intervention. The results showed an increase in the average knowledge score from 10.63 (SD ±2.85) to 17.18 (SD ±1.96) after the intervention, with a statistically significant difference (p < 0.001). The FAST method of education was proven effective in enhancing early stroke detection abilities among hypertensive patients. This intervention is recommended as an educational strategy in promotive programs within primary healthcare services.